Development and Wear Analysis of Al- Nano SiC Composite Automotive Cam. (2015) - Rana, R.S.; Purohit, Rajesh; Soni, V.K.; Das, S.
Abstract: Material science and engineering has experienced a tremendous growth in the field of Micron and nanocomposites developed with enhanced chemical, mechanical and physical properties. Cam has been fabricated by Ultrasonic assisted Stir casting process. Different weight % of Nano SiC (1, 2, 3 and 4 wt. %) were used for synthesis of composites and composite Cams. Hardness of composites was measured. Further Al-SiCp Composite cams have been tested for accelerated wear at different time intervals. Results shows that the Al-micron SiCp Composite Cam were having the almost same wear resistance as the existing Alloy steel Cam. However weight of composites cam was 1/3 of the alloy steel cam.